Robust Taylor rules in an open economy with heterogeneous expectations and least squares learnig - Mikael Bask; Carina Selander (Bank of Finland, 2007)
The aim of this paper is threefold: (i) to investigate if there is a unique rational expectations equilibrium (REE) in the small open economy in Gall and Monacelli (2005) that is augmented with technical trading in the foreign exchange market; (ii) to investigate if the unique REE is adaptively learnable in a recursive least squares sense; and (iii) to investigate if the unique and adaptively learnable REE is desirable in an inflation rate targeting regime in the sense that a low and not too variable CPI inflation rate in equilibrium is achieved. The monetary authority is using a Taylor rule when setting the nominal interest rate, and we investigate numerically the properties of the model developed. A main conclusion is that the monetary authority should increase (decrease) the interest rate when the CPI inflation rate increases (decreases) and when the currency gets stronger (weaker) to have a desirable rule that is robust with respect to the degree of technical trading in the foreign exchange market. Thus, the value of the currency is a better response variable than the output gap in the most desirable parametrizations of the interest rate rule.
URN:NBN:fi:bof-20140807577
Keywords: E52; F31; 330; determinacy; foreign exchange; inflation rate targeting regime; interest rate rule; robust monetary policy; technical trading